PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN - I Nyoman Resa Adhika1 (Jurnal Ilmiah Satyagraha, 2025)
Employees work because they want to achieve something, and people hopethat their work activities will lead them to a more satisfying situation than before. Jobsatisfaction is a psychological dimension that reflects a person's feelings about hisjob, namely his satisfaction with the suitability of his skills, abilities, and expectationsfor the job he holds. This study aims to explain the effect of workload, workenvironment, and compensation on employee job satisfaction at Cake Tha. Theresearch population is all employees of Cake Tha. The sample in this study were 51respondents. The data analysis technique used in this research is multiple linearregression analysis, which is tested using SPSS version 25. The results of this studyindicate that workload has a negative and significant effect on job satisfaction, whilethe work environment and compensation each have a positive and significant effecton employee job satisfaction at Cake Tha.